GIS-BASED ASSESSMENT OF GROUND WATER QUALITY FOR DRINKING PURPOSE BY WATER QUALITY INDEX APPROACHES IN BAHAWALPUR, PUNJAB - Ali Hassan; Haroon Rashid; Ahsan Sarfraz; Kashif Javed; Dawood Nawaz; Muhammad Faizan (Science Heritage Journal)
Groundwater pollution is a significant environmental issue globally, particularly in large cities, and trace heavy metals are the most significant groundwater pollutants. Pakistan is particularly affected by groundwater contamination, which poses a major threat to public health. Many industrial facilities in Pakistan discharge untreated wastewater into nearby drains, which has a direct impact on the quality of surface water, soil, and groundwater. Bahawalpur, the 11th most populous city in Pakistan, is the focus of this research, which examines how residential areas in the city affect groundwater. The research area was carefully studied, and groundwater sampling locations were collected from 45 distinct locations throughout Bahawalpur’s residential area. Groundwater samples were then analyzed for various parameters, including pH, turbidity, electrical conductivity, total dissolved solids, calcium, magnesium, iron, total hardness, total alkalinity, and chloride content. The results of these tests were compared to World Health Organization (WHO) recommendations, and the outcomes of the elements were displayed using ArcView GIS v10.7.1 and raster interpolation with IDW. The study found that the concentration of pollutants in groundwater exceeded the permitted level, and the water quality index for drinking water was determined to be only 65 percent in terms of pH, turbidity, electrical conductivity, iron, calcium, magnesium, total dissolved solids, total alkalinity, and total hardness. The characteristics of the groundwater did not comply with WHO standards. These findings suggest that there is a pressing need to address water pollution in Bahawalpur. The data collected and analyzed in this study could be used to design and construct a filtration plant facility to reduce water pollution in the area.